Fin failure tolerant control of agile air vehicle using feedback linearization - Asghar Ashrafifar; Mohsen Fathi Jegarkandi (Measurement + Control)
The probability of actuator lock, control surface damage, and thermal insulation failure on supersonic aircraft due to high speed and temperature is significant. Additionally, foldable fins are often used in missiles to increase the number of missiles that can be loaded onto a launcher and facilitate transportation, but this design presents the potential for malfunction and failure to open during flight. This study focuses on scenarios where control surfaces do not open or are partially damaged, leading to asymmetries and changes in the vehicle’s dynamics and aerodynamic model. The aim is to detect such failures and design a control system that can withstand these issues. To achieve this, the paper proposes an equivalent aerodynamic model representing the vehicle’s dynamics. The health of each fin is monitored using a nonlinear filter to estimate a parameter. Using separation theory, the dynamic system is divided into fast and slow subsystems, and a control signal for the faulty dynamics is designed based on back-stepping theory principles. Furthermore, the control allocation method is modified to accommodate the condition of the fins and generate the desired control moment. The proposed technique can quickly detect and isolate fin failures within seconds, while the designed controller effectively compensates for these failures.